Avian Diseases Transmissible to Humans - Michael A. Davis; Gary D. Butcher; F. Ben Mather (EDIS, 2015)
Anyone who keeps birds, whether as pets or as production animals, should be aware that certain avian diseases can be transmitted to humans. The seriousness of the disease in humans varies with human hosts’ age, overall health, and immune status as well as virulence of the organism, infective dose, and route of infection. This 4-page fact sheet is a major revision which discusses causes and symptoms of avian influenza (bird flu), chlamydiosis, salmonellosis, colibacillosis, encephalitis viruses, avian tuberculosis, Newcastle Disease, and cryptosporidiosis. Written by Michael A. Davis, Gary D. Butcher, and F. Ben Mather, and published by the UF Department of Animal Sciences. Original publication date: August 1997, revised August 2015.